2021
DOI: 10.1097/pts.0000000000000826
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Catheter Guidewire Retention: Lessons From England’s Never Event Database

Abstract: ObjectivesGuidewire retention during central venous catheter (CVC) insertion is considered a “never event.” We analyzed the National Health Service England Never Event database (2004–2015) to explore the process of guidewire retention and identify potential preventative measures.MethodsWe performed a systematic analysis of reported retained guidewire incidents by 3 independent reviewers.ResultsThere was a rising frequency of reported retained CVC guidewires, with an average of 2 never events per month. Only 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Thirteen cases of retained guidewires were reported in the UK Never Events database in 2019. 14 Despite the introduction of safety measures, including checklists, retained guidewires still occur because all preventable measures rely on the operator remembering to perform the safety check. Ultimately, CVC design equipment changes have been proposed to prevent guidewire retention.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen cases of retained guidewires were reported in the UK Never Events database in 2019. 14 Despite the introduction of safety measures, including checklists, retained guidewires still occur because all preventable measures rely on the operator remembering to perform the safety check. Ultimately, CVC design equipment changes have been proposed to prevent guidewire retention.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded another 337 articles after reviewing the full-text citations largely because they neither identified individual NEs nor specified an existing framework (47%), or because they were non-scholarly (eg, media releases; 30%). Thus, our analyses were based on 367 articles 3 4 7–11 18–377. A full list of these articles and the information we extracted from them are found in online supplemental tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The safe and swift removal of foreign bodies assumes particular significance. Previous reports of guidewire retention predominantly arise from instances where a broken guidewire inadvertently slipped into the bloodstream during procedures such as coronary angiography[ 1 , 7 ]. Unlike those reported cases, the guidewire in the present study was inadvertently left within the abdominal cavity, with only one similar case reported in the literature[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guidewires are pivotal in various clinical procedures, encompassing guidance, support, and exchange. While the retention of guidewires within the body is typically deemed uncommon, recent estimates suggest that, on average, two instances of guidewire retention during central venous catheter insertion arise each month[ 1 ]. Nevertheless, only one case involving the retention of guidewires within the abdominal cavity has been previously documented[ 2 ].…”
Section: Introductionmentioning
confidence: 99%